Epizootic of sarcoptic mange in raccoon dogs (Nyctereutes procyonoides) in relation to population density - SUGIURA, Natsuko; DOI, Kandai; KATO, Takuya; MORITA, Tatsushi; HAYAMA, Shin-ichi (Journal of Veterinary Medical Science, 2018)
To examine outbreaks of mange in raccoon dogs (Nyctereutes procyonoides) with respect to population density, we analyzed camera trap videos, and isolated mites from raccoon dog carcasses. In a camera trapping survey, we categorized the skin condition of raccoon dogs, and used a number of independent videos to calculate the relative abundance index (RAI). The RAI of raccoon dogs with alopecia increased following an increase in the RAI of those without alopecia. Among 27 raccoon dog carcasses, 12 showed mange-compatible skin lesions. Sarcoptes scabiei was isolated from 11 of these raccoon dogs, indicating that sarcoptic mange was endemic in our study area. Therefore, a high relative population density may be a factor underlying epizootics of sarcoptic mange in raccoon dogs.